Towards a Structured AI-Integrated Academic Writing Guideline: Perspectives from the Academic Community - Udi Samanhudi; Dina Rachmawati (Journal of English Language Studies, 2025)
This study is part of an ongoing project to design an AI-integrated academic writing guideline to strengthen the existing curriculum of academic writing at a public university in Banten, Indonesia. Specifically, it seeks to capture the perspectives of students and lecturers on the use of generative AI, particularly ChatGPT, in their writing practices. Grounded in Swales’ English for Specific Purposes (ESP) and Systemic Functional Linguistics (SFL), the research employed a qualitative case study involving semi-structured interviews, a focus group discussion, and textual analysis of student essays. Participants included ten second-year students and two senior academic writing lecturers. Findings reveal that both groups perceive ChatGPT as a “double-edged” tool: it enhances linguistic accuracy, idea development, and structural organization, yet also raises concerns about dependency, ethical boundaries, and the erosion of critical and creative thinking. While students demonstrated strong enthusiasm toward AI integration, they also expressed uncertainty regarding its appropriate use, highlighting the urgent need for explicit guidance and institutional policy. The study argues for the development of a localized AI-integrated academic writing guideline that promotes not only technical competence but also reflective, ethical, and critical engagement with AI. These insights contribute to ongoing debates on the role of generative AI in higher education and provide actionable implications for curriculum design, teacher training, and institutional policymaking in EFL contexts.